2014
DOI: 10.1155/2014/746506
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Interactions between Arbuscular Mycorrhizal Fungi and Biotic Stressors of Plants

Abstract: Naturally, simultaneous interactions occurred among plants, herbivores, and soil biota, that is, arbuscular mycorrhizal fungi (AMF), nematodes, and fungal pathogens. These multiple interactions play fundamental roles in driving process, structure, and functioning of ecosystems. In this study, we conducted a meta-analysis with 144 papers to investigate the interactions between AMF and plant biotic stressors and their effects on plant growth performance. We found that AMF enhanced plant tolerance to herbivores, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…The highly selected modern bread wheat T. aestivum, which does contain a historically introduced A. tauschii-derived D genome, added prior to later extensive domestication, strongly suppresses Nematoda, even compared to its abundance in bulk soil. It is possible that Glomeromycetes and Nematoda interact with each other (Yang et al, 2014), for example, it has been observed that mycorrhiza fungi, both directly and by priming plant defense, is able to reduce Nematoda gall formation (Hao et al, 2012). However, our experimental setup does not allow us to make any conclusions about their interactions above stated that their relative abundance seem to be correlated.…”
Section: Discussionmentioning
confidence: 88%
“…The highly selected modern bread wheat T. aestivum, which does contain a historically introduced A. tauschii-derived D genome, added prior to later extensive domestication, strongly suppresses Nematoda, even compared to its abundance in bulk soil. It is possible that Glomeromycetes and Nematoda interact with each other (Yang et al, 2014), for example, it has been observed that mycorrhiza fungi, both directly and by priming plant defense, is able to reduce Nematoda gall formation (Hao et al, 2012). However, our experimental setup does not allow us to make any conclusions about their interactions above stated that their relative abundance seem to be correlated.…”
Section: Discussionmentioning
confidence: 88%
“…There are several published articles showing the role of AMF in increasing plant tolerance against biotic stressors. The meta-analysis of 144 published papers clearly reveals that ( Yang et al, 2014 ). Considering the role AMF have in bioprotection, Gianinazzi et al (2010) described AMF as ‘health insurance’ of plants.…”
Section: Amf and Measurable Restoration Attributesmentioning
confidence: 99%
“…Soil microbes can affect the competitive ability of plants or mitigate competitive interactions (reviewed in Hodge & Fitter 2013). Associations with arbuscular mycorrhizal fungi tend to increase plant tolerance of negative biotic interactions, including herbivory and pathogens (Yang et al 2014). Increased investment in below-ground biomass by legumes that associate more strongly with rhizobia may affect their ability to tolerate herbivores (Heath & Lau 2011;Heath & McGhee 2012).…”
Section: E C H a N I S M S O F S E L E C T I O N O N P L A N T T R mentioning
confidence: 99%